Optimizing atrio‐ventricular delay in pacemakers using potentially implantable physiological biomarkers. Issue 4 (28th January 2022) - Keene, Daniel; Miyazawa, Alejandra A; Johal, Monika; Arnold, Ahran D; Ali, Nadine; Saqi, Khulat A; March, Katherine; Burden, Leah; Francis, Darrel P; Whinnett, Zachary I; Shun‐Shin, Matthew J
Abstract: Background: Hemodynamically optimal atrioventricular (AV) delay can be derived by echocardiography or beat‐by‐beat blood pressure (BP) measurements, but analysis is labor intensive. Laser Doppler perfusion monitoring measures blood flow and can be incorporated into future implantable cardiac devices. We assess whether laser Doppler can be used instead of BP to optimize AV delay. Methods: Fifty eight patients underwent 94 AV delay optimizations with biventricular or His‐bundle pacing using laser Doppler and simultaneous noninvasive beat‐by‐beat BP. Optimal AV delay was defined using a curve of hemodynamic response to switching from AAI (reference state) to DDD (test state) at several AV delays (40–320 ms), with automatic quality control checking precision of the optimum. Five subsequent patients underwent an extended protocol to test the impact of greater numbers of alternations on optimization quality. Results: 55/94 optimizations passed quality control resulting in an optimal AV delay on laser Doppler similar to that derived by BP (median absolute deviation 12 ms). An extended protocol with increasing number of replicates consistently improved quality and reduced disagreement between laser Doppler and BP optima. With only five replicates, no optimization passed quality control, and the median absolute deviation would be 29 ms. These improved progressively until at 50 replicates, all optimizations passed quality control and the median absolute deviation was only 13 ms. Conclusions: Laser Doppler perfusion produces hemodynamic optima equivalent to BP. Quality control can be automatic. Adding more replicates, consistently improves quality. Future implantable devices could use such methods to dynamically and reliably optimize AV delays.